The Red Sea under the Caliphal Dynasties, c. 639–1171. Issue 10 (10th August 2018) - Power, Timothy
Abstract: Students of world history will be familiar with the Red Sea as a strategic communications corridor linking the Mediterranean to the Indian Ocean. This paper examines the Red Sea region between the seventh and twelfth centuries, when it was ruled by a succession of Islamic caliphal dynasties, namely, the Umayyads, ʿAbbāsids, and Fāṭimids. It first sets out a sketch of the political history of the Red Sea and its constituent hinterland polities, including particularly Egypt, Sudan, al‐Ḥijāz, and Yemen, drawing attention to episodes and processes in which the Red Sea was significant. A section on Africa and Arabia explores the Red Sea as a zone of economic and social interaction; another section deals with the historic shift of Indian Ocean trade from the ʿAbbāsid Persian Gulf to the Fāṭimid Red Sea. Finally, the impact of the Red Sea on its constituent hinterland polities and the wider sweep of Islamic history is considered.